Feasibility of microRNA profiling in human inner ear perilymph. Issue 11 (1st August 2018) - Shew, Matthew; Warnecke, Athanasia; Lenarz, Thomas; Schmitt, Heike; Gunewardena, Sumedha; Staecker, Hinrich
Abstract : Hearing loss is common and caused by a wide range of molecular and cellular pathologies. Current diagnosis of hearing loss depends on a combination of physiologic testing, patient history, and in some cases genetic testing. Currently, no biopsy or equivalent procedure exists to diagnose inner ear disorders. MicroRNAs (miRNA) are short ribonucleic acids that regulate a variety of cellular processes. They have been found to be reliable markers for a variety of disease processes. In particular, a variety of miRNAs that are markers for neurodegenerative disease have been identified in cerebrospinal fluid. The aim of this study was to determine whether miRNAs could be identified in human perilymph potentially leading to the development of biomarkers for inner ear disease. Prospective sampling of human perilymph and its analysis were carried out. Patients undergoing surgery in which the inner ear is opened as part of the procedure (cochlear implantation, stapedectomy, labyrinthectomy) were recruited. A total of 2–5 μl of perilymph was collected and analyzed using Affymetrix GeneChip miRNA 4.0 microarrays. MiRNA common to all sampling approaches were selected. Analysis of miRNAs was carried out by evaluating miRNA targets in a cochlear transcriptome library using the Ingenuity Pathway Analysis software package. MiRNAs could be isolated from the perilymph of all patients. Evaluation of miRNAs shows the presence of miRNA populations that are predicted to interact with genes expressed in the inner ear. Additional analysis of miRNA populations shows that perilymph miRNAs could be linked to pathways associated with hearing disorders. Sampling of human perilymph is feasible and can potentially identify miRNAs associated with hearing disorders.